The Politics Of Corruption Eradication Law In The Aspect Of Anti-Corruption Education - Yunus Rahendra; Aryani Witasari (Universitas Islam Sultan Agung, 2021)
The purpose of this study is to explain the need for aspects of anti-corruption education provided in educational institutions. Currently, the government is still focused on the regulation of legislation, especially on efforts to strengthen law enforcement. However, efforts to eradicate corruption by breaking the chain of its emergence by providing anti-corruption education in educational institutions are a promising step if implemented optimally. Based on the above background, problems arise, namely how is the urgency of anti-corruption education, then how is the role of the government in anti-corruption education management. The research approach method used is normative juridical using secondary data. Data collection is done by collecting and analyzing library materials and related documents. Furthermore, the data from this study were analyzed qualitatively, namely by collecting research data to be processed which was then concluded to obtain information and answers to research problems. The conclusion of this research is the need for the role of the educational component to teach moral and ethical doctrine to students from an early age. In addition, the government's role is also important in supporting the implementation of anti-corruption education from the level of policy makers. Among them is the internalization of anti-corruption education in existing subject matter by updating the existing curriculum.